2020
DOI: 10.3390/antibiotics9060283
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation in Murine Models of Systemic Inflammation Induced by Gram-Positive and Gram-Negative Toxins

Abstract: Iron is an essential element for various physiological processes, but its levels must remain tightly regulated to avoid cellular damage. Similarly, iron plays a dual role in systemic inflammation, such as with sepsis. Leukocytes utilize iron to produce reactive oxygen species (ROS) to kill bacteria, but pathologically increased iron-catalyzed ROS production in sepsis can lead to damage of host cells, multi-organ failure and death. Temporary reduction in bioavailable iron represents a potential therapeutic targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Consistent with previous reports, LPS increased leukocyte adherence in intestinal submucosal venules [ 16 , 17 , 18 ]. LPS activates Toll-like receptor 4 (TLR4) and downstream inflammatory cascades that result in upregulation of adhesion molecule expression [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports, LPS increased leukocyte adherence in intestinal submucosal venules [ 16 , 17 , 18 ]. LPS activates Toll-like receptor 4 (TLR4) and downstream inflammatory cascades that result in upregulation of adhesion molecule expression [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to its antimicrobial activity, data from preclinical experimental models have indicated that DIBI has anti-inflammatory activity during sepsis [ 56 , 57 ]. Treatment with DIBI was able to reduce inflammation-associated markers (leukocyte activation, loss of capillary perfusion and tissue damage) after administration of lipotechoic acid from S. aureus and lipopolysaccharide from E. coli and K. pneumoniae [ 56 ].…”
Section: Iron Chelators As Antimicrobial Agentsmentioning
confidence: 99%
“…In addition to its antimicrobial activity, data from preclinical experimental models have indicated that DIBI has anti-inflammatory activity during sepsis [ 56 , 57 ]. Treatment with DIBI was able to reduce inflammation-associated markers (leukocyte activation, loss of capillary perfusion and tissue damage) after administration of lipotechoic acid from S. aureus and lipopolysaccharide from E. coli and K. pneumoniae [ 56 ]. Although the molecular mechanisms underlying the anti-inflammatory activity observed with DIBI are not fully understood, it has been hypothesized that is may be due to reduced iron-catalyzed reactive oxygen species production by leukocytes during sepsis [ 56 , 57 ].…”
Section: Iron Chelators As Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors describe two new multi-locus sequence typing (MLST)-based sequence types of K. pneumoniae [ 27 ]. In the second basic science article of this Special Issue, Fokam and colleagues examine iron chelation in murine models of systemic inflammation induced by Gram-positive and Gram-negative bacterial toxins [ 28 ]. This is a timely topic, given the recent development of cefiderocol, a novel antimicrobial agent for the treatment of Gram-negative bacteria with DTR that utilizes the iron transport system.…”
mentioning
confidence: 99%